3m-7=m+11

Simple and best practice solution for 3m-7=m+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-7=m+11 equation:



3m-7=m+11
We move all terms to the left:
3m-7-(m+11)=0
We get rid of parentheses
3m-m-11-7=0
We add all the numbers together, and all the variables
2m-18=0
We move all terms containing m to the left, all other terms to the right
2m=18
m=18/2
m=9

See similar equations:

| 45.36=38.06+c | | 60000=-x3+3x2+400x-600 | | 5(8-g)+g=55+11g | | K/6=k-2/4 | | 8r+3=11 | | 4(d-4+2)=3(d+1) | | 6-x/4=2 | | 2x+5=5x-21 | | 7x-3x+24=2x+4 | | 296=3.296p | | 2x+3×+4×=180 | | 4(d-4+2=3(d+1) | | 38=8+5n | | 4w^2+3w-280=0 | | 3x=(4x-2) | | 2y+63/5=19 | | 7n+8=4n+23 | | (t+4)^2-12(t+4)+35=0 | | X=-2|y|+4 | | 38=p/5-4 | | 12x-16=90 | | $0.75-$36.00=n | | (2w-16)•w=9216 | | (z-1)^2-64=0 | | X+24-9x=-2 | | 13=x÷4 | | 2x-24=-10× | | 5y^2-5=4 | | (x-2)/3=-12 | | h=-16(2)^2+32(2) | | -19-x=-6(3×+6 | | P(x)=-40x^2+1920x-132000 |

Equations solver categories